Preparation and Coordination Characterization of Glutathione-Zn2+ Complex - Zhou, Z.; Sang, L.Y.; Dong, L.C.; Xu, Y.; Zhou, X.H. (Asian Journal of Chemistry, 2011)
Glutathione (GSH)-Zn2+ complex was prepared using a dialysis-lyophilization method, the coordination ratio of the prepared complex was determined to be: GSH:Zn2+ » 2:1. IR, 1H NMR and atomic force microscope tests indicated that the binding sites between glutathione and Zn2+ are the carbonyl oxygen in the amide group (Cys residue) and sulfur atom in the thiol groups. A coordination structure of the complex was proposed according to the coordination ratio and the bonding sites of glutathione. Further investigation demonstrated that the capability of GSHZn2+ complex to restrain hydroxyl and super-oxide radicals is stronger than that of free glutathione molecule.